A hybrid nested partitions and simulated annealing algorithm for dynamic facility layout problem: a robust optimization approach. Issue 1 (2nd January 2021) - Khajemahalle, Leila; Emami, Saeed; Keshteli, Ramezan Nemati
Abstract: The dynamic facility layout problem (DFLP) deals with the arrangement of facilities/departments in a factory for different periods so that the location of the facilities can be changed from one period to another one. Traditionally, this problem is formulated to minimize the sum of material handling and rearrangement costs in the planning horizon by assuming that all parameters are deterministic. In this paper, we assume that the material flow between departments and rearrangement costs are uncertain and, accordingly, develop the robust counterpart (RC) of the DFLP model. The model is computationally intractable; therefore, we propose a hybrid algorithm based on nested partitions (NP) and simulated annealing (SA) algorithms, namely NP-SA. Moreover, we develop a heuristic algorithm to compute the values of the additional variables used in the RC model. The numerical results indicate that the NP-SA algorithm is very effective in giving a good solution in a short time. Furthermore, a simulation study demonstrates that, on average, robust solutions are better than nominal solutions.